(untitled) (Universal International Scientific Journal, 2026)
This article examines the challenges and opportunities of using artificial intelligence (AI) in foreign language teaching within the context of implementing digital technologies in modern education. The study analyzes how AI-based learning platforms can enhance students’ engagement, individualize the learning process, and improve the quality of language acquisition. Special attention is given to the pedagogical potential of AI tools, such as speech recognition, interactive exercises, automated feedback, and adaptive learning paths. The research also identifies key issues, including teachers’ digital competence, methodological support, and cognitive overload caused by excessive information. The findings demonstrate that methodically grounded and pedagogically guided use of AI in language education significantly contributes to the effectiveness and quality of learning outcomes.